1974
DOI: 10.1111/j.1471-4159.1974.tb06896.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VIVO CHANGES OF CEREBRAL CYCLIC ADENOSINE 3′,5′‐MONOPHOSPHATE INDUCED BY BIOGENIC AMINES: ASSOCIATION WITH PHOSPHORYLASE ACTIVATION

Abstract: The intravenous injection of adrenaline, isoprenaline and histamine to 4-6-day-old chicks resulted in a rapid increase in the cyclic AMP content of cerebral hemispheres that had been removed and frozen within 0.5 s using a freeze-blowing technique. Noradrenaline, dopamine, adenosine, 5-HT and acetylcholine did not significantly alter the nucleotide concentration in uiuo. Addition of adrenaline, isoprenaline and histamine to incubated chick cerebral cortex slices also increased the cyclic AMP content of the tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…In our studies, the effect ofVIP also was potentiated by isobutylmethylxanthine (not shown), suggesting that the glycogenolytic action of the peptide was mediated by cyclic AMP. In peripheral tissues (52), brain (23,24), neuroblastoma, and astrocytoma cell lines (25,26), cyclic AMP activates phosphorylase through a cascade of enzymatic phosphorylation steps, thus initiating glycogen degradation. This process, along with the inhibition of glycogen synthetase (26), ultimately results in a decrease in the cellular glycogen content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our studies, the effect ofVIP also was potentiated by isobutylmethylxanthine (not shown), suggesting that the glycogenolytic action of the peptide was mediated by cyclic AMP. In peripheral tissues (52), brain (23,24), neuroblastoma, and astrocytoma cell lines (25,26), cyclic AMP activates phosphorylase through a cascade of enzymatic phosphorylation steps, thus initiating glycogen degradation. This process, along with the inhibition of glycogen synthetase (26), ultimately results in a decrease in the cellular glycogen content.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have been published with regard to the various aspects of glycogen metabolism in glial and neuronal elements (23)(24)(25)(26)(27)(28). Furthermore, in a series of elegant biochemical and autoradiographic studies, Wolfe and Nicholls (29) have shown that a mechanism for ['4C]glucose uptake and the subsequent synthesis of ['4C]glycogen existed in glial cells and neurons of the leech central nervous system.…”
mentioning
confidence: 99%
“…Though the hypothalamus contains the most histamine in all species, in most of these histamine does not increase cAMP and excites rather than inhibits hypothalamic neurons, being inhibi tory to most other neurons. In the chicken brain, cAMP stimulation by histamine is blocked by metiamide (189) and not potentiated by adenosine (190). In guinea pig cerebral cortical or hippocampal slices, histamine effects are partly (50-80%) blocked by either H-1 or H-2 antagonists while both together completely block the response (186).…”
Section: Brain Adenylcyclase and Campmentioning
confidence: 96%
“…The activities of a few other nervous system enzymes have been shown to be associated with stimulation of cAMP levels. Brain glycogen phosphorylase activity is increased by agents that stimulate 3',5'-cyclic AMP levels (Edwards et al, 1974). Tyrosine hydroxylase purified from rat caudate nucleus incorporated 32P when incubated with a CAMP-dependent protein kinase in vitro, and a twofold increase in enzyme activity was also obtained (Joh et al, 1978).…”
Section: Phosphorylation Of Carbonic Anhydrase Andmentioning
confidence: 99%